AVAILABILITY OF AGRICULTURAL LAND AND FULFILLMENT OF POPULATION FOOD NEEDS IN URBAN REGION (Case Study of Pekalongan City, Tengah Jawa) - Imade Yoga Prasada; Masyhuri Masyhuri (Agricultural Socio-Economics Journal, 2020)
The availability of agricultural land in urban areas has an important role in ensuring the availability of food for the population. The urban sprawl phenomenon that occurs in urban areas encourages the availability of agricultural land to experience shrinkage over time. Therefore, this study aims to determine the trend of the development of the area of agricultural land in Pekalongan City, and its impact on the fulfillment the food needs of the population. This study used a sample of urban areas in Pekalongan City using purposive sampling method and the data used are secondary data sourced from the Central Bureau of Statistics and the Food Security and Extension Agency (BKPP) in 1989 until 2017. The data used in this study are data agricultural land area, rice production, population, and consumption per capita of rice in Pekalongan City, as well as factor data for conversion of rice to rice. Furthermore, all data is processed and then analyzed using trend analysis. The results showed that the area of agricultural land in Pekalongan City is decreasing over time. Moreover, it followed by the quantity of rice offered that also have a downward trend. In addition, the demand trend of the population's rice also declined due to the decline of rice consumption per capita population in Pekalongan City during the period 1989 to 2017.